Switching to a protease inhibitor-containing, nucleoside-sparing regimen (lopinavir/ritonavir plus efavirenz) increases limb fat but raises serum lipid levels: results of a prospective randomized trial (AIDS clinical trial group 5125s) - Tebas, Pablo; Zhang, Jiameng; Yarasheski, Kevin; Evans, Scott; Fischl, Margaret A; Shevitz, Abby; Feinberg, Judith; Collier, Ann C; Shikuma, Cecilia; Brizz, Barbara; Sattler, Fred (Journal of acquired immune deficiency syndromes (1999), 2007)
Subcutaneous limb fat loss continues to be one the most troubling side effects of long-term antiretroviral regimens. Nucleoside analogues and protease inhibitors (PIs) have been linked to the development of this complication. We evaluated the effects of nucleoside-sparing and PI-sparing regimens on fat distribution, bone mineral density, and metabolic parameters in 62 subjects, who were not selected for lipoatrophy, with advanced HIV (nadir CD4 count <or=200 cells/mm or HIV RNA level >or=80,000 copies/mL) and an undetectable HIV viral load. Participants were randomized to switch their initial successful antiretroviral regimen to open-label lopinavir/ritonavir (LPV/r) at a dose of 533/133 mg twice a day and efavirenz (EFV) at a dose of 600 mg/d (the nucleoside-sparing arm) versus EFV and 2 nucleoside analogues (the PI-sparing arm). At week 48, the median change in limb fat in the nucleoside-sparing arm was 562 g (6%, interquartile range [IQR]: -218-1186 g) versus a loss of -242 g (-4%, IQR: -539-452 g) in the nucleoside-containing PI-sparing arm (P = 0.086). At the time of last observation (median = 102 weeks, IQR: 73-152 weeks), a median gain of 782 g (10%, IQR: -380-1168 g) of limb fat was noted in the nonnucleoside arm (n = 22) versus a loss of 850 g (-15%, IQR: -1270 to -526 g) in the nucleoside-containing arm (n = 25; P = 0.002). The switch to a nucleoside-sparing combination antiretroviral regimen (LPV/r + EFV) was associated with significant improvement in limb fat. These results provide additional evidence that nucleoside analogues are important in the progressive limb fat loss that characterizes antiretroviral treatment and that switching medications can significantly improve this complication. This option has to be carefully balanced with the potential to increase serum lipid levels and the trend to increase virologic failure.